Cloud computing: The beliefs and perceptions of Swedish school principals - Lim, Nena; Gronlund, A.; Andersson, A.; Andersson, A. (Pergamon Press, 2015)
This article highlights the importance of cloud computing in education and explores the environment surrounding schools' adoption of cloud services. Based on the technology leadership literature, the study investigates the beliefs and perceptions of school principals toward cloud computing. Principals of primary and high schools in Sweden were invited to participate in an online survey and 342 responses were received. Results suggest principals of Swedish schools believe the main benefits of cloud computing to be its ability to allow users to access data and software anywhere as long as there is Internet access and its ability to facilitate sharing of learning materials and data. The biggest obstacle is the concerns about security and privacy of data. Moreover, principals of public schools perceived more obstacles than those of private schools. Results also indicate a misalignment of beliefs between the principals and other stakeholders such as the municipalities' information technology (IT) departments and lawyers. This lack of shared views is another major obstacle for cloud computing adoption. Results provide useful firsthand information to municipalities, school administrators, and teachers on the beliefs and perceptions of the principals toward this new technology.